Prediction of post-operative range of motion using intra-operative soft tissue balance in total knee arthroplasty with navigation. (2nd January 2015) - Hasegawa, Masahiro; Takagita, Hisatsugu; Sudo, Akihiro
Abstract: This study evaluated the influence of intra-operative soft tissue balance on post-operative range of motion in patients undergoing posterior-stabilized total knee arthroplasty with navigation. After implantation of all components in 31 consecutive patients, the joint component gap was measured manually with the knee at 0°, 90°, and 120° as guided by a navigation system. We designated soft tissue balance as the absolute difference between varus stress and valgus stress (medio-lateral laxity). Changes in medio-lateral laxity were calculated from 120° to 90°, 120° to 0°, and 90° to 0°. Correlations among post-operative flexion angles and pre-operative flexion angles, intra-operative flexion angle after implantation, soft tissue balance, and the changes were analyzed. The mean pre- and post-operative knee flexion angles were 114 ± 20° and 127 ± 9°, respectively. The mean intra-operative flexion angle was 137 ± 6°. The post-operative flexion angle was positively correlated with the pre-operative flexion angle and intra-operative flexion angle after implantation. The change in soft tissue balance between 120° and 90° showed a positive correlation with the post-operative flexion angle. In conclusion, Assessment of intra-operative soft tissue balance could predict post-operative flexion angle.